VARIABILITY AND CORRELATION OF AGRONOMIC CHARACTERS OF MUNGBEAN GERMPLASM AND THEIR UTILIZATION FOR VARIETY IMPROVEMENT PROGRAM Lukman Hakim - Lukman Hakim (Indonesian Journal of Agricultural Science, 2008)
Information on the variability and correlation between agronomic characters of mungbean accessions with their yield are important for supporting breeding program of the plant. A total of 350 mungbean accessions were evaluated at Muara Experimental Farm, Indonesian Center for Food Crops Research and Development, Bogor, during the dry season of 2005. The experiment was conducted in a completely randomized block design with three replications. Each accession was planted in two rows of 5 m long. Plant spacing was 40 cm x 20 cm, two plants per hill. Correlation and path coefficient analyses were used to quantifythe magnitude of the relationship between yield components and grain yield. The variability among the accessions was significant for most of the characters studied, especially for days to maturity, plant height, pods per plant, and seed size. Among the yield components, the number of pods per plant and plant height positively correlated with the grain yield, but theseed size negatively correlated with grain yield. The direct effects of the number of pods per plant and plant height on seed yield as indicated by path coefficient were the highest, while other causal effects were small or negative. Yield variation (1- R2) attributable to the nine yield component variables was slightly high (61.23%), which means that mungbean accessions with high grain yield should have sufficient plant height and high number of pods per plant. Therefore, these parameters (number of pods per plant and plant height) can be used as the selection criteria in mungbean breeding program. These criteria can be visualized during bulk selection on the early generation stage of F2 to F4, and subsequently on line development of individual plant (pedigree) of F5.